Sedimentary provinces of the world ([Tulsa, Okla. : American Association of Petroleum Geologists, 1984)
Shows locations of giant and subgiant oil fields, areas with undeveloped discoveries, areas lacking gas or oil fields, areas with sediments on oceanic crust, and continental and marine locations with little or no sediment.
Grid BBST (Meter)
Peta Geologi (PG)
Keywords: Oil fields -- Maps; Gas fields -- Maps; Sedimentary basins -- Maps